Analysis of School Financial Management on The Management of School Operational Assistance Funds In Elementary Schools In Talang Kelapa District, Banyuasin Regency - Akhmad Deny Arianto; Nurlina; Sri Wahyu Indrawati (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aimed to analyze school financial management in the implementation of School Operational Assistance (BOS) fund management and its influence on the timeliness of Accountability Report (SPJ) submission in elementary schools in Talang Kelapa District, Banyuasin Regency. A qualitative case study approach was employed involving school principals, BOS treasurers, school operators, and the district BOS verification team as research informants. Data were collected through observation, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that BOS fund management has generally been implemented in accordance with government regulations through RKAS planning, financial administration, reporting, and supervision. Nevertheless, several challenges remain, including limited human resource competencies, dual-role assignments, frequent regulatory changes, unstable digital systems, and incomplete supporting documents. Schools with effective administrative systems, strong coordination, and active principal supervision demonstrated better reporting performance and timely SPJ submission. This study contributes to educational management by emphasizing that strengthening human resource capacity, improving digital financial systems, and enhancing internal coordination are essential strategies for improving transparency, accountability, and efficiency in BOS fund management.